Herbal Medicines: Socio-Demographic Characteristics And Pattern Of Use By Patients In A Tertiary Obstetrics And Gynaecology Unit (Journal of Science and Technology, 2016)
Herbal medicines are used by patients, mostly without the knowledge of their Doctors and other Health providers. The presentation, course and outcomes of the patient's condition may thus be affected. There has been a lot of concern recently about the use of herbal medicines. The Ghana Food and Drugs Board has come out with a strong campaign aimed at regulating the advertisement of medicinal products, especially herbal medicines. Unfortunately, little is known about the pattern of use of herbal medicines by patients attending our hospitals. This cross-sectional descriptive survey with in depth interviews wascarried out to determine the socio-demographic characteristics and the pattern of herbal medicine use by patients in the Obstetrics and Gynaecology Department in Komfo Anokye Teaching Hospital. More than 50% of those interviewed said they used herbal medicines with liquid preparations being the most frequently used. About 25% of these preparations were administered orally and the rectal and vaginal routes were also used. It is recommended that documentation of herbal medicine use is done wheneverpatients are seen in health institutions. Further studies are needed to find out about the use of herbal medicines in the general population since it would play a major role in the Ghana Ministry of Health's goals of integrating herbal medicine use into health delivery and providing comprehensive health services for all. There is also the need for collaboration between the Department of Herbal Medicine and other Departments in the College of Health Sciences at the Kwame Nkrumah University of Science and Technology.